(untitled) (Research, Society and Development, 2021)
Objective: To chemically characterize Spondias mombin L. extracts and to evaluate the in vitro antimicrobial activity of these extracts on Enterococcus faecalis and Pseudomonas aeruginosa. Material and methods: Both extracts were submitted to phytochemical prospecting and thin layer chromatography (TLC) analysis prior to determination of Minimum Inhibitory Concentration (MIC), Minimum Inhibitory Adhesion Concentration (MIAC) and Bactericidal Kinetics (BK). The Student’s t-test was used to compare MIC results at the 5% significance level. The chemical characterization, MIAC and BK data were analyzed descriptively. Results: Phenolic compounds, flavonoids, tannins and saponins were detected in the extracts. The hydroethanolic extracts in different concentrations showed statistically superior inhibitory bacterial growth activity (p <0.05) compared to the control against the two investigated microorganisms, whereas the aqueous extracts (also in different concentrations) was statistically superior (p <0.05) to the control only against Pseudomonas aeruginosa. The anti-adherent effect of both extracts was superior to that of the control for P. aeruginosa, and similar to that for E. faecalis. In their crude and diluted concentrations, aqueous and hydroethanolic extracts showed bactericidal action within the first two to four hours of contact with the bacteria. Conclusion: Spondias mombin L. extracts in different concentrations showed superior antimicrobial activity than 0.12% chlorhexidine digluconate against the microorganisms with this activity associated to the chemical characterization of these extracts.